Pemberian Probiotik Multispesies dalam Media Budi Daya Ikan Lele Dumbo untuk Mencegah Penyakit Motile Aeromonads Septicemia (ADDITION OF MULTISPECIES PROBIOTICS IN THE CULTURE MEDIUM OF AFRICAN CATFISH TO PREVENT THE MOTILE AEROMONADS SEPTICEMIA DISEASE) - Fidyandini, Hilma Putri; Yuhana, Munti; Lusiastuti, Angela Mariana (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
One of the disease that often led to mortality in catfish resulting in harvest failure is Motile AeromonadsSepticemia (MAS) caused by infection of Aeromonas hydrophila. To avoid this situation, the preventionand control of disease is very crucial. An environmentally friendly approach acceptable in aquaculture isthe use of probiotics to control the pathogenic infection. African catfishes used in the study weighted of1,97±0,7g/fish, and were maintained in the aquarium size of 56x39x34 cm3filled with 30 liters of waterwith stock density of 25 fishes . Probiotic was given daily for 28 days. This research was consisted of 6treatments; (A) AH26 NAR103 CFU/mL, probiotics ND2 CefR 105 CFU/mL dan P23 CipR 105 CFU/mL ; (B)AH26 NAR103 CFU/mL, probiotics ND2 CefR 103 CFU/mL dan L1k TetR 103 CFU/mL; (C) AH26 NAR103CFU/mL, probiotics P23 CipR 104 CFU/mL dan L1k TetR 104 CFU/mL; (D) AH26 NAR103 CFU/mL, probioticsND2 CefR 105 CFU/mL, P23 CipR 105 CFU/mL dan L1k TetR 105 CFU/mL; (K+) AH26 NAR103 CFU/mL, without probiotics; (K-) Without the addition of probiotics and without AH26 NAR in the media. Eachtreatment has 3 replications. The results showed that the combination of probiotics ND2CefR103CFU/mLand L1k TetR103CFU/mLcan supressedA. hydrophila cell density up to 40% lower, induced immuneresponses (hematocrit level and respiratory burst activity) and increased the survival rate of catfishuntilthe end of the research.
Keywords: multispecies probiotic; Clarias gariepinus; motile aeromonads septicemia